Transformation of Back-Offices Function to Support a Culture of Innovation and Intellectual Capital Deployment - Oleynikova, I. (Університет «КРОК», 2018)
The most important attribute of intellectual capital is the company's ability to innovate, which makes it possible to gain sustainable competitive advantage. In addition to critical parts of the intellectual capital management system, such as the human capital management system and the knowledge management system, another important aspect is to be considered -the formation of the company's ability to be adaptive and agile. So, if a key competence-the ability to innovate-is a function of the front office, then the creation of adaptive capacity, which is a certain combination of human capital and a knowledge management system, manifests itself in a back-office meaning. The main back-office function is to support generation of innovations and their implementation through key competencies that ensure the rapidalterations of all processes and structures that are supposed to change.The main purpose of the research is to create company expertise, organizational structure, processes, performance measurement and ateam that will be able to maintain steady changes and remain successful. It is obvious that the key component of such a company will be a well-formed team with the necessary skills, knowledge, and competencies, a team whose propensity for transformation is one of its basic characteristics, a team for which resistance to change is unacceptable. The goal of this research is to show how implementing culture of transformation in the back-office helps to promote innovations and improve the company's performance.Additionally, monetary assessment of back-office performance is done to demonstrate what exactly the business will receive in terms of market share, financial results, and company value.

У цій статті йдеться про можливості трансформації функції бек-офісів з метою підтримки культури інновацій та розгортання інтелектуального капіталу. Безперечно, найважливішим атрибутом інтелектуального капіталу на сьогодні є здатність компанії до інновацій, що дозволяє отримати стійку конкурентну перевагу. На додаток до критично важливих частин системи управління інтелектуальним капіталом, таким як система управління людським капіталом і система управління знаннями, слід враховувати ще один важливий аспект - формування здатності компанії бути адаптований і гнучкою. Таким чином, якщо ключова компетенція - здатність до інновацій - є функцією фронт-офісу, то створення адаптивного потенціалу, що представляє собою певну комбінацію людського капіталу та системи управління знаннями, проявляється в бек-офісі. Основна функція бек-офісу полягає в підтримці генерації інновацій та їх реалізації через ключові компетенції, які забезпечують швидкий зміни всіх процесів і структур, які повинні змінитися. Основна мета дослідження полягає в тому, щоб створити досвід компанії, організаційну структуру, процеси, вимір продуктивності і команду, яка зможе підтримувати стійкі зміни і залишатися успішною. Очевидно, що ключовим компонентом такої компанії буде добре сформована команда з необхідними навичками, знаннями та компетенціями, команда, схильність до трансформації якої є однією з її основних характеристик, команда, для якої опір змінам стане неприйнятним. Мета дослідження представленого у цій статті - показати, як відбувається впровадження культури трансформації в бек-офісі, що сприяє просуванню інновацій та підвищенню ефективності компанії. Крім того, проводиться грошова оцінка ефективності роботи бек-офісу, щоб продемонструвати, що саме отримає бізнес з точки зору частки ринку, фінансових результатів та вартості компанії.
Keywords: ntellectual capital; culture of innovation; back-office transformation; knowledge management system; performance; value added operations; інтелектуальний капітал; культура інновацій; трансформація бек-офісу; система управління знаннями; результативність; операції з доданою вартістю